Adrenal sensitivity to stress is maintained despite variation in baseline glucocorticoids in moulting seals. (11th March 2015) - Champagne, Cory; Tift, Michael; Houser, Dorian; Crocker, Daniel
Abstract : Select hormones, like glucocorticoids, could be informative markers of stress in animals. To be useful, however, baseline and stressed state hormone concentrations must be described. We therefore evaluated the timing and magnitude of stress hormone release by simulating an acute stressor in a marine mammal, the northern elephant seal. Abstract : Stressful disturbances activate the hypothalamic–pituitary–adrenal (HPA) axis and result in the release of glucocorticoid (GC) hormones. This characteristic stress response supports immediate energetic demands and subsequent recovery from disturbance. Increased baseline GC concentrations may indicate chronic stress and can impair HPA axis function during exposure to additional stressors. Levels of GCs, however, vary seasonally and with life-history stage, potentially confounding their interpretation. Our objective was to evaluate HPA axis function across variations in baseline GC levels. Northern elephant seals show substantial baseline variation in GC levels during their annual moulting period. We therefore conducted measurements early, in the middle and at the end of moulting; we simulated an acute stressor by administering adrenocorticotrophic hormone and evaluated the changes in circulating hormones and metabolites over the following 2 h. The stress response was characterized by increases in both cortisol and aldosterone ( F 7, 105 = 153 and 25.3, respectively; P < 0.001). These hormones increased in parallel and the slopes of their relationship varied by study group, suggesting they are regulated in a co-ordinated manner during acute stress in this species. There was no detectable difference in the total release of cortisol or aldosterone among study groups, indicating that the HPA axis remained sensitive to stimulation by adrenocorticotrophic hormone despite varying baseline levels of GCs. Acute stress influenced carbohydrate and fat metabolism in all study groups, but protein catabolism was affected to a far lesser degree. These findings suggest that elephant seals, and potentially other pinniped species, are resilient to moderate variations in baseline GC levels and remain capable of mounting a response to additional stressors.